KENANGAN MASA KECIL DI PESISIR PANTAI SELAYAR SEBAGAI SUMBER IDE PENCIPTAAN KARYA SENI LUKIS - A Faisal Darmawan; Syamsiar Syamsiar Syamsiar (Texture: Visual Art and Culture Journal, 2023)
Childhood memories are something that cannot be avoided. Childhood memories provide many very meaningful life experiences as if they attract the heart to return to the past. The experience of the author who was born and grew up in the Selayar coastal area where almost all of his activities are in direct contact with the coast. This condition gave the writer an idea to create a painting entitled: Childhood Memories of Selayar Beach Children.The creation of this final project work uses stages based on L.H. Chapman's theoretical basis regarding the process of work creation, which states 3 stages of work creation, namely, 1). Efforts to find an idea (inception of an idea), 2). Refine, develop and solidify initial ideas (elaboration and refinement, 3). Visuals in a medium (tension in a medium). The technique used in creating the work in the creation of this work is the plaque and sweep technique which refers to the way of creating impressionist works which depict the impression of form through strong color processing and lighting, dark light, and the addition of accents.From the arrangement of visual elements and composition of visual elements, 8 works were produced entitled: Ruwat Bumi, Ruwat Sukerta Banyumasan, Ebeg Banyumasan, Lenggeran, Kothekan Lesung, Sintrenan, Wayang Jemblung, and Cowong Wulan Sari Wungu.